Actinomyces pyogenes CAUSANTE DE ABORTO EN BOVINOS - Araínga R., Mariluz (2003)
A case of bovine fetal abortion due to Actinomyces pyogenes in a dairy herd of Cieneguilla valley of Lima, Peru is reported. A bovine fetus of four monts of gestation was aborted and submitted for laboratory examination. Macroscopic lesions in fetal tissues were not found with the exception of numerous white foci up to 1mm in diameter in diameter in the lungs. Various fetal tissue samples were collected for virologic, bacteriologic and histopathologic examinations. Bovine viral diarrhea virus (BVDV) and Neospora caninum antigen were ruled out by immunohistochemistry but, pure colonies of A. pyogenes were isolated from the lung and other fetal tissues. The microscopic examination showed moderate to severe bronchopneumonia associated to pyogenic bacterium. The isolation of A. pyogenes, the macro and microscopic lesions and the absence of BVDV an N. caninum antigen in the fetal tissues indicated the A. pyogenes as a causative agent of this fetal abortion.